2020
DOI: 10.3390/pathogens9020124
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and Infection Dynamics of Multi-Host Amdoparvoviral and Protoparvoviral Carnivore Pathogens

Abstract: Amdoparvovirus and Protoparvovirus are monophyletic viral genera that infect carnivores. We performed surveillance for and sequence analyses of parvoviruses in mustelids in insular British Columbia to investigate parvoviral maintenance and cross-species transmission among wildlife. Overall, 19.1% (49/256) of the tested animals were parvovirus-positive. Aleutian mink disease virus (AMDV) was more prevalent in mink (41.6%, 32/77) than martens (3.1%, 4/130), feline panleukopenia virus (FPV) was more prevalent in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 53 publications
1
41
0
1
Order By: Relevance
“…The FPV-positive rate in Canadian otters was almost 30%. Hence, it was suggested that otters might be a principal maintenance host for FPV enabling viral persistence and serving as a source for other susceptible species (18). In this study, the serum from otter had SN titer <20 in the SN test against FPV Fe-P2 strain.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The FPV-positive rate in Canadian otters was almost 30%. Hence, it was suggested that otters might be a principal maintenance host for FPV enabling viral persistence and serving as a source for other susceptible species (18). In this study, the serum from otter had SN titer <20 in the SN test against FPV Fe-P2 strain.…”
Section: Discussionmentioning
confidence: 59%
“…FPV has been known to infect other species like raccoon dogs, foxes, minks, African wild cats, cheetahs, and honey badgers (5,6). Furthermore, FPV was still frequently found in wild animals like otters, minks, and martens (18,19). The FPV-positive rate in Canadian otters was almost 30%.…”
Section: Discussionmentioning
confidence: 99%
“…The two minks, as in other mustelids, are small carnivores with characteristically elongated bodies. Mustelids contain around 60 known species, including, in addition to mink, otter, ferret, polecat, marten, ermine, badger, sable, and wolverine ( Canuti et al, 2020 ). Several mustelids, including mink, sable, and ermine, have been hunted since prehistoric times for their fur.…”
Section: Ecology Of Mink Worldwidementioning
confidence: 99%
“…Several microorganisms can affect mustelids ( Canuti et al, 2020 ). The most studied are those commonly found in mink on fur farms.…”
Section: Mink and Contagious Diseasesmentioning
confidence: 99%
“…SVVs have experienced great change in their nucleotide composition over the past ten years and have been identified in different hosts and tumor cells. Mutational pressure from several animal hosts accelerates the frequency of recombinant mutations in SVV (Canuti et al, 2020). Cross-host transmission may have led to a rapid increase in the rate at which mutant stress has an effect.…”
Section: Disscussionmentioning
confidence: 99%